Decorated bacteria and the application in drug delivery - Wu, Feng; Liu, Jinyao (Advanced drug delivery reviews, 2022)
[Display omitted] The use of living bacteria either as therapeutic agents or drug carriers has shown great potential in treating a multitude of intractable diseases. However, cells are often fragile to unfriendly environmental stressors and limited by inadequately therapeutic responses, leading to unwanted cell death and a decline in treatment efficacy. Surface decoration of bacteria has emerged as a simple yet useful strategy that not only confers bacteria with extra capacity to resist environmental threats but also endows them with exogenous characteristics that are neither inherent nor naturally achievable. In this review, we systematically introduce the advancements of physicochemical and biological technologies for surface modification of bacteria, especially the single-cell surface decoration strategies of individual bacteria. We highlight the recent progress on surface decoration that aims to improve the bioavailability and efficacy of therapeutic bacterial agents and also to achieve enhanced and targeted delivery of conventional drugs. The promises along with challenges of surface-decorated bacteria as drug delivery systems for applications in cancer therapy, intestinal disease treatment, bioimaging, and diagnosis are further discussed with respect to future clinical translation. This review offers an overview of the advances of decorated bacteria for drug delivery applications and would contribute to the development of the next generation of advanced bacterial-based therapies.